Analysis of asymptotics for a model of nonlinear oscillations of the absolute elastic weightless string - Lavcel, Olga; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2009)
The mathematical model of string nonlinear oscillations is presented. To found the asymptotic solution of the problem an averaging scheme was constructed in cited latest work of the second author. In this paper a methodology for construction special form soliutions of the system is proposed.